Multisensory Learning: Improving Conceptual Understanding Through an Intuitive Sensory Approach - Nurjanah; Imelda Christine Kansil; Imas Masturoh; Dedi Hanwar (Journal of Pedagogi, 2024)
Learning in the modern era requires an adaptive approach to accommodate the diversity of students' learning styles to enhance the effectiveness of education. One innovative approach is multisensory learning, which combines visual, auditory, and kinesthetic sensory stimulation to aid students' understanding of concepts, particularly in abstract subjects such as science and mathematics. This study employs a descriptive qualitative approach with a case study method at a junior high school that has implemented this approach. The research subjects include 30 students, five teachers, and three education experts, selected purposively. Data were collected through in-depth interviews, classroom observations, and document analysis. The findings indicate that the multisensory approach effectively addresses the diversity of students' learning styles, enhances concept comprehension, and fosters an inclusive learning environment. This approach also supports students with special needs, such as dyslexia and sensory processing disorders, and improves students’ long-term information retention. Teachers play a significant role in the successful implementation of this method through training and innovative strategies. Thus, the multisensory approach has a positive impact not only on material comprehension but also on students' enthusiasm for learning and positive peer communication. This study recommends the importance of support in teacher training and the provision of resources to optimize the application of multisensory learning